Purification, characterization and probiotic proliferation effect of exopolysaccharides produced by Lactiplantibacillus plantarum HDC-01 isolated from sauerkraut - Yu, Liansheng; Ye, Guangbin; Qi, Xintong; Yang, Yi; Zhou, Bosen; Zhang, Yunye; Du, Renpeng; Ge, Jingping; Ping, Wenxiang (Frontiers in Microbiology, 2023)
In this study, an exopolysaccharides (EPS)-producing strain of Lactobacillus plantarum HDC-01 was isolated from sauerkraut and the structure, properties and biological activity of EPS were assessed. The molecular weight of EPS is 2.505×106 Da. The fourier transform infrared spectrometer (FT-IR) and nuclear magnetic resonance (NMR) results show that EPS is a glucopyranose linked by an α-(1→6) glycosidic bond and contains an α-(1→3) branching structure. X-ray diffraction (XRD) shows that the structure of EPS appears in an amorphous and non-crystalline state. Scanning electron microscope (SEM) and atomic force microscopy (AFM) shows that EPS has a smooth and compact surface with a number of protrusions of varying lengths and irregularly shaped material. EPS has good thermal stability, water holding capacity, milk coagulation ability. Moreover, EPS also promotes the growth of human intestinal bacteria and improves the human intestinal environment. The results of this experiment expand the potential applications of L. plantarum EPS and provide a theoretical basis for subsequent industrial applications.